Observation of a metal-centered B2-Ta@B18− tubular molecular rotor and a perfect Ta@B20− boron drum with the record coordination number of twenty. Issue 10 (17th January 2017) - Li, Wan-Lu; Jian, Tian; Chen, Xin; Li, Hai-Ru; Chen, Teng-Teng; Luo, Xue-Mei; Li, Si-Dian; Li, Jun; Wang, Lai-Sheng
Abstract : A B2 -Ta@B18 − tubular molecular rotor and a Ta@B20 − boron drum with the record coordination number of twenty were observed via a joint experimental and theoretical investigation. Abstract : A tubular molecular rotor B2 -Ta@B18 − (1 ) and boron drum Ta@B20 − (2 ) with the highest coordination number of twenty in chemistry are observed via a joint photoelectron spectroscopy and first-principles theory investigation.